Investigations on microstructure and properties of Ti-Nb-Zr medium-entropy alloys for metallic biomaterials. (June 2022) - Hu, Meichen; Wang, Li; Li, Gen; Huang, Qianli; Liu, Yang; He, Junyang; Wu, Hong; Song, Min
Abstract: In this study, three medium entropy alloys (MEAs), TiNbZr, Ti1.5Nb1.5Zr and Ti1.5NbZr1.5 were designed and investigated to be applied as biomedical materials. The results showed that the alloys prepared by arc melting have a typical dendrite microstructure, caused by elemental segregation during solidification. With composition changes, the partition of the constituting elements behaves differently. The microstructure inhomogeneity and chemical segregation could be greatly reduced by homogenization treatment. The MEAs show good compressive ductility (>40%) and yield strength comparable to or even superior to those of the commercially used biomedical alloys (e.g., 316 stainless steel and pure titanium), which are mainly contributed from the solid-solution strengthening effect. In addition, these MEAs exhibit acceptable Young's modulus ranging from 80 to 93 GPa by nano-indentation tests. The alloys also show excellent corrosion resistance in the phosphate buffer saline (PBS) solution and favorable cyto-compatibility, which are comparable to or even superior to pure titanium and/or Ti-6Al-4V alloys. Based on these properties, the Ti-Nb-Zr MEAs show a promising potential in biomedical applications. The results in this study could be instructive for further alloy design of such biomedical MEAs. Highlights: Three medium entropy alloys (MEAs) for biomaterials were designed. The microstructure of the MEAs is composed of a single bcc phase. The MEAs exhibit excellent corrosion resistance in PBS. The MEAs manifest excellent biocompatibility comparable to CP-Ti.